Pengembangan Pakuwon Mall Sebagai Destinasi Wisata Belanja dan Wisata Perjalanan di Kota Surabaya - Evie Muliasari Dewi (PolimdoSains, 2019)
Pakuwon Mall is the biggest Mall in Indonesia with glamour concept as International Mall. Pakuwon Mall as a modern and tourist destination, especially for shopping, culinary and family entertainment destination. As a shopping destination, it has been filled with branded tenants such as H & M, Pull and Bear, Bonia, Stradivarius, Marks and Spencer, etc. For culinary destinations has presented a full meal tenants such as culinary domestic and overseas menu, except that there are unique characteristics of Pakuwon Mall which bring the atmosphere of street food inside mall, which brought the food counter food truck in area Food Society. However, the existence of Pakuwon Mall has not been well known among both domestic and International tourists. There is lack of cooperation between the owner, local government, Tourism Department and Tour Agents in promotional efforts. Supposedly with good cooperation and promotion of tourism, Surabaya can be recognized by many domestic and international travelers through Pakuwon Mall as a modern shopping tourist destination. Branded promotion of tourism and tours and traveling package includes the shopping tour in Pakuwon Mall. This research apply observation that was done directly on site in Pakuwon Mall, taking note of the observation, taking photo in some important places and tenants which showing the best sides of Pakuwon Mall.